2020
DOI: 10.21203/rs.3.rs-34635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of SARS-CoV-2 patients: a French cross-sectional study in primary care

Abstract: Background: The early identification of patients suffering from SARS-CoV-2 infection in primary care is of outmost importance in the current pandemic.Aim: To gain a better understanding of the specific symptoms of SARS-CoV-2 infection in primary care.Design and setting: We conducted a cross-sectional study between March 24 and May 7, 2020, involving consecutive patients undergoing RT-PCR testing in two community-based laboratories in Lyon (France) for a suspicion of COVID-19.Methods: We examined the associatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Regarding our results of the reported symptoms, loss of smell (anosmia) was the strongest indicator of SARS-CoV-2, followed by fever, shortness of breath, myalgia, cough, nausea, diarrhea, and coryza. The significant influence of loss of smell and cough is in line with previous studies carried out in high-income countries such as the US and UK [2,1214], and the influence of fever, myalgia, and nausea was pointed as significant in some studies [13,14], but others noted as not associated [2,12]. Regarding sore throat, diarrhea, and shortness of breath, previous studies observed that they are not significant predictors for the SARS-CoV-2 infection [2,1214].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding our results of the reported symptoms, loss of smell (anosmia) was the strongest indicator of SARS-CoV-2, followed by fever, shortness of breath, myalgia, cough, nausea, diarrhea, and coryza. The significant influence of loss of smell and cough is in line with previous studies carried out in high-income countries such as the US and UK [2,1214], and the influence of fever, myalgia, and nausea was pointed as significant in some studies [13,14], but others noted as not associated [2,12]. Regarding sore throat, diarrhea, and shortness of breath, previous studies observed that they are not significant predictors for the SARS-CoV-2 infection [2,1214].…”
Section: Discussionsupporting
confidence: 89%
“…Sebo and colleagues [14] studied a sample of 1,543 primary care patients tested in two laboratories in the Lyon area (France) and found that the two symptoms most strongly associated with a positive test were loss of taste (ageusia) and loss of smell and that the combination of these symptoms resulted in an even stronger association (i.e., the odds of having a positive test were six times greater than the odds of having a negative test). A recent literature review of studies analyzing the presence of loss of taste and smell in SARS-CoV-2 infected patients concluded that, from a total of 10,818 patients, 8,823 presented ageusia (81.6%) and 8,088 presented anosmia (74.8%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding our results of the reported symptoms, loss of smell (anosmia) was the strongest indicator of SARS-CoV-2, followed by fever, shortness of breath, myalgia, cough, nausea, diarrhea, and coryza. The significant influence of loss of smell and cough is in line with previous studies carried out in high-income countries such as the US and UK [6,[24][25][26], and the…”
Section: Plos Onesupporting
confidence: 90%
“…influence of fever, myalgia, and nausea was pointed as significant in some studies [25,26]. However, other authors noted it as not associated [6,24].…”
Section: Plos Onementioning
confidence: 95%
“…Dry nose, loss of taste and/or smell, and muscle pain are frequent complaints of COVID-19 patients who visit their family practitioner [41, 42], while hospitalised patients [4] usually complain of fever, dry cough, dyspnoea, chest pain, fatigue, and myalgia. Almost 95% of the infected people present mild or moderate symptoms that do not necessitate hospital-based care.…”
Section: Discussionmentioning
confidence: 99%